Modelling of the workpiece geometry effects on Ti–6Al–4V linear friction welds - McAndrew, Anthony; Colegrove, Paul A.; Addison, Adrian C.; Flipo, Bertrand C. D.; Russell, Michael J.; Lee, Lucie Alexandra (Elsevier, 2015)
Linear friction welding (LFW) is a solid-state joining process that is finding increasing interest from industry for the fabrication of titanium alloy (Ti–6Al–4V) preforms. Currently, the effects of the workpiece geometry on the thermal fields, material flow and interface contaminant removal during processing are not fully understood. To address this problem, two-dimensional (2D) computational models were developed using the finite element analysis (FEA) software DEFORM and validated with experiments. A key finding was that the width of the workpieces in the direction of oscillation (in-plane width) had a much greater effect on the experimental weld outputs than the cross-sectional area. According to the validated models, a decrease of the in-plane width increased the burn-off rate whilst decreasing the interface temperature, TMAZ thickness and the burn-off required to remove the interface contaminants from the weld into the flash. Furthermore, the experimental weld interface consisted of a Widmanstätten microstructure, which became finer as the in-plane width was reduced. These findings have significant, practical benefits and may aid industrialisation of the LFW process.